2017
DOI: 10.1212/wnl.0000000000004608
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic brain injury may not increase the risk of Alzheimer disease

Abstract: Traumatic brain injury (TBI) commonly occurs in civilian and military populations. Some epidemiologic studies previously have associated TBI with an increased risk of Alzheimer disease (AD). Recent clinicopathologic and biomarker studies have failed to confirm the relationship of TBI to the development of AD dementia or pathologic changes, and suggest that other neurodegenerative processes might be linked to TBI. Additional studies are required to determine the long-term consequences of TBI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
1
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 19 publications
4
53
1
4
Order By: Relevance
“…In this study, analysing 110 individuals from the University of Manchester Longitudinal Study of Cognition in Normal Healthy Old Age cohort who had consented to brain donation, we found no association between incidence of cognitive impairment and HI‐LOC nor did we find any correlation between HI‐LOC and regional AD pathology or any of the three established measures of the neuropathology associated with AD: CERAD score, Thal phase, or Braak stage. Although the present study is limited by the self‐reporting nature of HI‐LOC and lack of knowledge of exact date and nature of head injury, our findings mirror those found in the two larger, well‐powered clinicopathological studies and suggest that HI‐LOC may not be a risk factor for increased severity of AD‐associated neuropathological lesions.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In this study, analysing 110 individuals from the University of Manchester Longitudinal Study of Cognition in Normal Healthy Old Age cohort who had consented to brain donation, we found no association between incidence of cognitive impairment and HI‐LOC nor did we find any correlation between HI‐LOC and regional AD pathology or any of the three established measures of the neuropathology associated with AD: CERAD score, Thal phase, or Braak stage. Although the present study is limited by the self‐reporting nature of HI‐LOC and lack of knowledge of exact date and nature of head injury, our findings mirror those found in the two larger, well‐powered clinicopathological studies and suggest that HI‐LOC may not be a risk factor for increased severity of AD‐associated neuropathological lesions.…”
Section: Discussionsupporting
confidence: 81%
“…Recently, it has been suggested that large, robust clinicopathological and biomarker studies, which avoid the usual limitations of self‐reported TBI in already cognitively impaired individuals, have failed to confirm the relationship of TBI to the development of AD dementia or AD pathology. The present study aims to further investigate the relationship of TBI and AD pathology in the elderly.…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis of 32 studies by Li and colleagues [6] demonstrated that repetitive head impact (RHI) significantly increases the relative risk of developing dementia and AD; however, recent publications indicate that TBI may not increase the risk of AD [12]. To further complicate the issue, TBI has also been shown to increase the risk for the onset other proteinopathies such as Lewy Body dementia [1], whilst the presence of multiple proteinopathies in individuals has been associated with advanced age [11].…”
mentioning
confidence: 99%
“…The link between TBI and dementia is supported by some large cohort studies (Guo et al, 2000;Plassman et al, 2000) including the demonstration of a dose-response relationship between injury severity and increased risk of Alzheimer's disease and dementia. Other studies have not found this association (Weiner et al, 2017). However, there is evidence for broader links between TBI and neurodegeneration, including microinfarcts, synucleinopathies and Parkinson's disease (Crane et al, 2016;Dams-O'Connor et al, 2016).…”
Section: Testing Specific Hypotheses About Functional Brain Plasticitmentioning
confidence: 97%